Teaching in Basic Education in times of pandemic: actions, pedagogical strategies and challenges faced in the 2020 school year of the Integral School Professor Ana Cristina Rolim Machado (Research, Society and Development, 2020)
This article consists of reporting the experience of the teaching team of the School of Integral Education Professor Ana Cristina Rolim Machado, in the city of João Pessoa / Paraíba, during remote education due to social isolation due to the pandemic of COVID-19. Knowing the importance of Education for the integral development of the individual and the need for a new adaptation to the context, with this work we aim to disseminate the actions, pedagogical strategies, resources used, the participation of families and the challenges faced in the academic year of 2020. Where , facing an atypical year, this teaching unit managed to maintain and carry out the programming of didactic-pedagogical activities, planned at the beginning of the current year, making the necessary changes for remote education, through work based on the organization, observing the realities and redesign of their actions, guaranteeing the subjective right inherent to children and adolescents: education. Supporting us on the concepts and theories related to education, teaching and the teaching-learning relationship, taking into account the Resolutions that guided the teaching process in the current context, such as Resolutions: No. 001/2020 of CME / JP and No. 002/2020, Law No. 14,040 / 2020, the Federal Constitution and the National Education Guidelines and Bases Law (LDB) No. 9394/96.